SMART technologies is an objective factor of the instrumental competences formation - Broslavska, H. (Problems of Engineer-Pedagogical Education, 2021)
The article proved that the instrumental competencies of students can be formed by teachers of higher educational establishments, if they use SMART technologies at their classes during the educational process. Teachers should not forget that ‘smart technologies’ will help to provide high-quality and effective teaching to applicants for education, motivate and attract them to creative, research, educational and scientific activities. During SMART education students’ ability is formed for: independent studying the material of the disciplines (according to the curriculum), because they can use electronic materials recorded in video mode, as well as lectures, practical exercises and tests stored by teachers online on their own sites, blogs; participating in development projects, etc. SMART-technologies contribute to the formation of new opportunities for educators, not previously mentioned in education, with the help of which they can: • share their own experience, acquired during professional activities, with others; • increase and improve their professional level, knowledge and skills; • engage more in scientific research and analysis; • save time at the preparation of educational material (lectures, practical and seminars) and the creation of scientific projects; • be a regular participant of your own developed content, etc. In the process of distance learning, which was fully during quarantine (from 03/12/2020 until the end of the academic year 2019-2020, all educational istablishments were closed as a result of a mass disease of the population with coronavirus infection - Covid-19), the problem of many Ukrainian teachers was found out - lack of preparedness for e-learning, distance learning; lack of ability to use SMART-technologies for the implementation of the educational process; lack of understanding of the importance of SMART education for the formation of instrumental competencies among applicants for education of higher educational establishments in our country. To solve these problems, it is necessary to show by examples how distance learning occurs, what knowledge students get when SMART technologies are used.